Entrepreneurial Marketing Theory: Current Developments and Future Research Agenda - Tayyab Amjad; Shamsul Huda Abdul Rani; Shiza Sa'atar (SEISENSE (PRIVATE) LIMITED, 2020)
Purpose- Entrepreneurial Marketing (EM) research has progressed rapidly over the last decade due to its effectiveness in highly competitive markets and uncertain conditions. However, the theory development in the EM domain is inadequate as yet. Due to this, the higher education institutions are also using outdated curricula to teach EM, as the new theories contribute towards the development of curricula. Thus, to assist in upgrading the EM curricula, we have examined the theory development over the last decade in the domain of EM. Design/Methodology- A systematic and in-depth review and analysis of over a decade’s EM literature has been done. Findings- Five major yet specific gaps are identified, and accordingly, we have proposed future research directions.